Peramalan Inflasi dengan Menggunakan Metode Arima: Studi di Indonesia - Tuti Eka Asmarani (Journal on Education, 2023)
The paper contains inflation forecasts using the Autoregressive Integrated Moving Average (ARIMA) method. The data used is Consumer Price Index data from January 2014 to March 2022. Using an optimistic scheme, inflation in 2023 is predicted to be 3.833%. The inflation projection is also within the national inflation projection range set by the government of 3% ± 1% or 2.0 – 4.0 percent in 2023.